Effectiveness of the Rapid Eye Movement Sequential Therapy Program in Reducing Post-Traumatic Stress Disorders in Individuals with Obsessive-Compulsive Disorder: A Sample of Mothers of Children with Special Needs Referred from Psychological Clinics in Kha - Bakhita Muhammad Zain Ali Muhammad (Journal of Psychology and Behavior Studies, 2024)
The study aimed to reveal the effectiveness of the Rapid Eye Movement Desensitization and Reprocessing (EMDR) program in reducing post-traumatic stress disorder among patients with obsessive-compulsive disorder (among a sample of mothers of children with special needs referred from psychiatric clinics in Khartoum). The study sample consisted of (14) mothers, who were intentionally selected from those attending psychiatric clinics in Khartoum, and suffering from obsessive-compulsive disorder as a result of post-traumatic stress disorder after being informed that their children have special needs. Their ages ranged between (35-40) years. Participation in the treatment program was approved based on the psychiatrists' orientations for them to attend the program to complete treatment after stopping medication. The Yale-Brown Obsessive Compulsive Scale was used and applied to the study sample before and after the program, as well as during follow-up. To achieve the study objectives, the EMDR program was applied to reduce post-traumatic stress disorder symptoms. It was prepared by the researcher and lasted for two months from January 1st (2023) until the end of February of the same year. The researcher applied the study tools before and after the program. The data was analyzed using the Statistical Package for Social Sciences (SPSS). The study reached the following results: The first hypothesis indicated statistically significant differences at the significance level (α=0.05) in obsessive thoughts among the study sample between the pre-test and post-test due to the EMDR program. The training program showed an effectiveness of (74.7%) in reducing their obsessive thoughts. The result of the second hypothesis also indicated statistically significant differences at the significance level (α=0.05) in compulsive acts among the sample between the pre-test and post-test, attributed to the EMDR program. The training program showed an effectiveness of (74.9%) in reducing the compulsive acts associated with post-traumatic stress disorder among the sample. The follow-up results indicated no statistically significant differences at the significance level (α=0.05) in obsessive thoughts among the sample between the post-test and follow-up test. There were also no statistically significant differences at the significance level (α=0.05) in compulsive acts among the sample between the post-test and follow-up test, indicating the effect and continued effectiveness of the training program during the follow-up stage. In light of these results, the study recommended conducting further studies on the effectiveness of the EMDR program in reducing post-traumatic stress disorder symptoms in patients with obsessive-compulsive disorder with a sample of males or other age groups to reduce their obsessive-compulsive acts.